The Role of Autonomous and Controlled Motivation in Exercise Intentions of Participants in a Mass Cycling Event - Willem, Annick; De Rycke, Jens; Theeboom, Marc (Frontiers in Psychology, 2017)
Purpose: This study used self-determination theory to examine the role of participants’ autonomous and controlled motivation to exercise and to participate in a challenging mass cycling event and investigated whether the event enhanced intended and actual exercise behavior among the participants. Method: Two hundred and twenty-eight subjects, having participated in the cycling event, completed a questionnaire shortly after the event and again four months later. The questionnaire measured self-reported cycling and exercise activity, training in preparation of the event, motivation to participate in the event, motivation to exercise, and future exercise intentions due to the event. Results: Results showed that most participants were very active in cycling and other sports. The expected positive effect of autonomous motivation on exercise intentions and behavior could not be confirmed in our study. Multiple regression analyses revealed that the event had an enhancing effect on exercise intentions shortly after the event among participants that scored higher on controlled motivation to exercise (β =0.15) and to participate (β =0.15); also, participants were more satisfied with the event (β=0.19) and had followed a preparation program before the event (β=0.15). However, intentions and exercise behavior distinctively dropped four months after the event. Conclusions: Events aiming to enhance their participants’ exercise behavior need to attract less active participants and need to make additional efforts to prevent relapse in intentions and exercise behavior.